2017
DOI: 10.1111/imcb.1035
|View full text |Cite
|
Sign up to set email alerts
|

Separate roles of IL‐6 and oncostatin M in mouse macrophage polarization in vitro and in vivo

Abstract: Arginase-1 (Arg-1)-expressing M2-like macrophages are associated with Th2-skewed immune responses, allergic airway pathology, ectopic B16 melanoma cancer growth in murine models, and can be induced by Oncostatin M (OSM) transient overexpression in vivo. Here, we compare OSM to the gp130-cytokine IL-6 in mediating macrophage polarization, and find that IL-6 overexpression alone (Ad vector, AdIL-6) did not induce Arg-1 protein in mouse lungs at day 7, nor ectopic melanoma tumor growth at day 14, in contrast to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
24
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 47 publications
7
24
3
Order By: Relevance
“…We have also demonstrated that IL‐6 directly regulates macrophage pro‐fibrotic phenotype when combined with IL‐4/IL‐13 and substantiates lung fibrosis in the animal model . More recently, we also showed that of the gp130 cytokines IL‐6, oncostatin M, and leukemia inhibitory factor, IL‐6 was the only cytokine to directly mediate M2 macrophage programming in vitro and was associated with M2 macrophage accumulation in ectopic melanoma tumor growth in vivo . As these macrophages were hyperpolarized with the addition of IL‐6, it provided a unique way to study mechanisms and organelles involved in the polarization process.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…We have also demonstrated that IL‐6 directly regulates macrophage pro‐fibrotic phenotype when combined with IL‐4/IL‐13 and substantiates lung fibrosis in the animal model . More recently, we also showed that of the gp130 cytokines IL‐6, oncostatin M, and leukemia inhibitory factor, IL‐6 was the only cytokine to directly mediate M2 macrophage programming in vitro and was associated with M2 macrophage accumulation in ectopic melanoma tumor growth in vivo . As these macrophages were hyperpolarized with the addition of IL‐6, it provided a unique way to study mechanisms and organelles involved in the polarization process.…”
Section: Introductionmentioning
confidence: 66%
“…2 More recently, we also showed that of the gp130 cytokines IL-6, oncostatin M, and leukemia inhibitory factor, IL-6 was the only cytokine to directly mediate M2 macrophage programming in vitro and was associated with M2 macrophage accumulation in ectopic melanoma tumor growth in vivo. 3 As these macrophages were hyperpolarized with the addition of IL-6, it provided a unique way to study mechanisms and organelles involved in the polarization process. Interestingly, the IRE1/XBP1 arm of the unfolded protein response (UPR) is thought to play a role in the differentiation of various cell types, and this is believed to include monocyte to macrophage transition, 4 eosinophil maturation, 5 dendritic cell survival 6 and B-cell to plasma cell differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…have previously been shown in isolation, their work highlights the detrimental cross‐talk between OSM, IL‐6 and M2 activation in the context of tumor metastases and tissue invasion. Although IL‐6 is often regarded as pro‐inflammatory cytokine, data emerging over the last twenty years, including the present work, challenge this simplified scenario and underline the context‐dependent nature of IL‐6 contribution to pathology . IL‐6 appears to augment the activation phenotype of macrophages imparted by other environmental cues .…”
mentioning
confidence: 64%
“…On the other hand, macrophages have been shown to promote tumor growth and facilitate metastases . In this issue of Immunology & Cell Biology Dubey et al . report a collaborative network of glycoprotein 130 (gp130) binding cytokines and STAT‐6‐mediated activation that drives macrophages to promote tumor growth.…”
mentioning
confidence: 99%
See 1 more Smart Citation